Simbiosis Mutualistis (PAI Dan Pendidikan Nasional) - Yuhana, Nihayatul Laili (STAI Miftahul Ula Nganjuk, 2015)
Abstract: Education is a conscious attempt adults to guide and direct the personality and ability of the students in formal or informal education. Islamic religious education is